2022
DOI: 10.3389/fimmu.2022.834316
|View full text |Cite
|
Sign up to set email alerts
|

Absolving COVID-19 Vaccination of Autoimmune Bullous Disease Onset

Abstract: As a perfect example of what we mean, we would like to cite the case of a 75-year-old male with type-II diabetes mellitus treated with gliptins, who developed bullous pemphigoid (BP) 48 h after receiving the first dose of the Comirnaty Pfizer-BioNTech vaccine. Physical examination revealed widespread tense blisters on erythematous skin. Histological examination and direct immunofluorescence findings confirmed the diagnosis of BP. Discontinuation of gliptins resulted in prompt clinical improvement, and the cuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
1
8
0
2
Order By: Relevance
“…This may, therefore, raise the question as to whether a true relationship between COVID‐19 vaccines and the new occurrence of pemphigus actually exists. 7 However, the case we present here, as well as the case reported by Solimani et al 8 help shed some light on this concern. We believe that the close association of COVID‐19 vaccination with the acute onset of pemphigus in our patient, as well as the exacerbation following subsequent administration of the vaccine, is more than a coincidence.…”
supporting
confidence: 68%
“…This may, therefore, raise the question as to whether a true relationship between COVID‐19 vaccines and the new occurrence of pemphigus actually exists. 7 However, the case we present here, as well as the case reported by Solimani et al 8 help shed some light on this concern. We believe that the close association of COVID‐19 vaccination with the acute onset of pemphigus in our patient, as well as the exacerbation following subsequent administration of the vaccine, is more than a coincidence.…”
supporting
confidence: 68%
“…Immunopathological features were typical, but anti-BP230 autoantibody was remarkably reduced ( 22 ). It should be noted that some authors argue against the casualty relation between the SARS-CoV-2 vaccine and AIBDs as they recorded no increase in disease incidence in the year of vaccination ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon could slightly anticipate BP development without significantly modifying the disease incidence. On the other hand, as some studies reported, it is not unconceivable that COVID-19 vaccines may induce a suitable environment to make these subjects more prone to drug-induced BP, as reported in some case of dipeptidyl peptidase IV inhibitors users (21)(22)(23). Finally, although the meaning of the association between COVID-19 vaccines and AIBDs remains to be elucidated, we hope that Kasperkiewicz and Tukaj speculations, together with our observations, will be able to stimulate the scientific community to design additional investigations on this topic.…”
Section: The Real-life Clinical Observations Are Valuablementioning
confidence: 98%